Rehabilitation treatment of multiple sclerosis - Duan, Haoyang; Jing, Yuling; Li, Yinghua; Lian, Yawen; Li, Jianfang; Li, Zhenlan (Frontiers in Immunology, 2023)
Multiple sclerosis is a slowly progressive disease, immunosuppressants and other drugs can delay the progression and progression of the disease, but most patients will be left with varying degrees of neurological deficit symptoms, such as muscle weakness, muscle spasm, ataxia, sensory impairment, dysphagia, cognitive dysfunction, psychological disorders, etc. From the early stage of disease to the stage of disease progression, professional rehabilitation treatment can reduce the functional dysfunction of multiple sclerosis patients, improve neurological function, and reduce family and social burden. With the development of various new rehabilitation technologies such as transcranial magnetic stimulation, virtual reality technology, robot-assisted gait training and remote rehabilitation, the advantages of rehabilitation therapy in MS treatment have been further established, and more treatment means have also been provided for patients.